The Optimalisasi Kapasitas Sumber Daya Manusia Hijau dalam Upaya Pelestarian Kualitas Lingkungan Berkelanjutan - Firdaus, Vera; Wulandari, Indah Apriliana Sari; Sudarso, Satrio; Maulidah, Ummul; Mutawakkil, Rizqy (Forum Kerjasama Pendidikan Tinggi, 2025)
This community service project aims to strengthen Green Human Resource (Green HR) capacity through internal campaigns and awareness-raising among herbal MSMEs in Desa Keplaksari and Pagotan, Jombang Regency. The methods employed include educational presentations, distributing campaign posters and stickers, providing sustainability education and processing waste from date seeds, as well as evaluating with pre- and post-tests. The results show that participants’ comprehension scores increased from an average of 45 to 77, awareness of cleanliness and waste management rose from approximately 20% to 80%, and satisfaction was high regarding the clarity and practical benefits of the material. The program shifted perceptions of waste from burden to business opportunity and fostered a green work culture among herbal MSMEs. Limitations such as small sample size, short duration, and not all follow-up implementation stages being completed are acknowledged. This study implies that Green HR and internal campaigns can be effective strategies to enhance environmental and economic sustainability at the MSME community level.